Effects of the epidemic and obstacle factors on the evolution of livelihood resilience of scenic farm households: a case study of the Wulingyuan scenic area, China - Wu, Jilin; Liu, Shuiliang; Xue, Keke; Zuo, Jinyou; Li, Li; Guo, Derong (Frontiers in Sustainable Food Systems, 2025)
IntroductionInvestigating the dynamic transformation of livelihood strategies of scenic farm households affected by COVID-19 is required for farmers to cope with external influencing factors, optimize their livelihoods, and ensure the sustainable development of scenic farm households’ livelihoods.MethodsThis study analyzes 364 farm households in five tourist villages in the Wulingyuan Scenic and Historic Area of Zhangjiajie City and establishes an index system to evaluate farm household livelihood resilience based on buffering, learning, and self-organizing capacities. The obstacle degree model is used to analyze resilience in the normal tourism stage (2019), epidemic disruption stage (2021), and tourism recovery stage (2023). The evolution characteristics of livelihood resilience and obstacle factors of farm households in the scenic area are assessed in the three stages and for different livelihood strategies.ResultsThe results show the following. (1) The epidemic significantly affected farmers’ livelihood resilience index. It was the highest in the normal tourism stage (0.449), followed by the tourism recovery stage (0.415) and the epidemic disruption stage (0.395). (2) The livelihood resilience indices of the four types of farm households had a clustered distribution and were relatively low. While there is considerable variability in the composition of health and education within farm households, and the livelihood resilience of farmers with different livelihood strategies was imbalanced. (3) The per capita forest land area (B2), skill training opportunities (L4), borrowing opportunities (S3), and migrant work (entrepreneurship) (S4) significantly affected the livelihood resilience of different types of farm households in different stages.DiscussionThis study enhances the dynamic assessment of farmers’ livelihood resilience at the micro level, providing a valuable decision-making reference for addressing external disturbances, such as epidemics, and implementing diversified livelihood strategies.